The Fiction of Junot Díaz: Reframing the Lens - Ostman, Heather (Rowman & Littlefield Publishers, 2016)
The influence of Latin American writers—as well as other immigrant writers and their first-generation peers—has reframed the literary lens to include multiple views and codify the shift away from the tradition of white male writers who formed the core of the American literary canon for generations. Junot Díaz is one of the most prominent and influential writers in contemporary American literature. A first-generation Dominican American, the New Jersey native is at the forefront of a literary renaissance, portraying the significant demographic shifts taking place in the United States. In The Fiction of Junot Díaz: Reframing the Lens, Heather Ostman closely examines the linguistic, popular culture, and literary references woven throughout Díaz’s fiction, including the short story collections Drown and This Is How You Lose Her, as well as the Pulitzer prize–winning novel The Brief Wondrous Life of Oscar Wao. Ostman also considers Díaz’s work as it relates to issues of identity, citizenship, culture, aesthetics, language, class, gender, and race. By exploring how Díaz reframes the immigrant narrative—highlighting his innovative linguistic and genre-based approach—Ostman provides crucial insights into how Díaz’s writings relate to key issues in today’s world. The Fiction of Junot Díaz will be of interest to scholars and students of the immigrant experience as well as fans of this gifted writer.